Evaluasi Pengakuan Pendapatan Atas Perusahaan Real Estate Berdasarkan PSAK NO.44 - Yosmar Ilham; Irawan Irawan; Evi Yuniarti (Politeknik Negeri Lampung, 2020)
The writing of this final project aims to evaluate the recognition of PT ABC revenue in 2018 whether it is in accordance with PSAK No.44. PT ABC's revenue recognition is performed using the Deposit Method. The evaluation was carried out on 2 types of financial statements, namely the income statement and the 2018 financial position report. Based on the evaluation of revenue recognition according to PSAK No.44, the results were obtained which stated that PT ABC had not yet recognized revenue because there were no customers who paid off their houses and buildings. still under construction, the company records money from customers as unearned revenue. According to PSAK No.44 all money originating from consumers is recognized as income received in advance as long as the buying and selling process has not been completed. So that the records made by the company are in accordance with PSAK No.44